Salvaging Exposed Cochlear Implants - Khalid Arab, MD, FRCSC (Wolters Kluwer, 2021)
Background:. The cochlear implant (CI) procedure is one of the most efficient surgical options for the management of patients suffering from severe bilateral sensorineural hearing loss. Notably, CI exposure is one of the most commonly reported complications. Herein, we report our experience in the management of three patients with CIs complicated by implant exposure. Methods:. We present a retrospective review-based case series of three patients with exposed CIs requiring soft tissue coverage who were referred to plastic surgery care. These patients underwent their CI procedures at a university hospital specializing in ear, nose, and throat, after which they were referred for plastic surgery care at our university hospital for reconstruction after exposure. Each patient was managed through different surgical techniques based on the size, site, and condition of the surrounding tissue. The management options are discussed in this article. Results:. Three patients with exposed cochlear implants were treated with different surgical techniques. During the 1-year follow-up period, the patients made an uneventful recovery with fully functional cochlear implants. Conclusions:. The management of CI extrusion with local scalp flaps can constitute an effective and reliable option to salvage CI with a good prognosis and a lower incidence of exposure recurrence. Optimal results for establishing effective soft tissue coverage can be achieved by choosing the appropriate technique according to the clinical presentation.